Effects of long-term methylphenidate treatment in adolescent and adult rats on hippocampal shape, functional connectivity and adult neurogenesis. (19th November 2015) - van der Marel, K.; Bouet, V.; Meerhoff, G.F.; Freret, T.; Boulouard, M.; Dauphin, F.; Klomp, A.; Lucassen, P.J.; Homberg, J.R.; Dijkhuizen, R.M.; Reneman, L.
Highlights: Methylphenidate (MPH) has different effects in young vs. adult rats. MPH impairs object recognition in adolescent rats, but not adults. MPH induces depressive-like behavior in adult rats, but not adolescent rats. MPH induces opposite effects on neurogenesis, and hippocampal shape. These findings are highly relevant for patients treated with MPH for attention deficit hyperactivity disorder (ADHD). Abstract: Methylphenidate (MPH) is a widely prescribed stimulant drug for the treatment of attention deficit hyperactivity disorder (ADHD) in children and adolescents. Its use in this age group raises concerns regarding the potential interference with ongoing neurodevelopmental processes. Particularly the hippocampus is a highly plastic brain region that continues to develop postnatally and is involved in cognition and emotional behavior, functions known to be affected by MPH. In this study, we assessed whether hippocampal structure and function were affected by chronic oral MPH treatment and whether its effects were different in adolescent or adult rats. Using behavioral testing, resting-state functional MRI, post-mortem structural magnetic resonance imaging (MRI), and immunohistochemistry, we assessed MPH's effects on recognition memory, depressive-like behavior, topological features of functional connectivity networks, hippocampal shape and markers for hippocampal neurogenesis and proliferation. Object recognition memory was transiently impaired in adolescent treated rats, while in animals treated during adulthood, increased depressive-like behavior was observed. Neurogenesis was increased in adolescent treated rats, whereas cell proliferation was decreased following adult treatment. Adolescent treated rats showed inward shape deformations adjacent to ventral parahippocampal regions known to be involved in recognition memory, whereas such deformations were not observed in adult treated animals. Irrespective of the age of treatment, MPH affected topological features of ventral hippocampal functional networks. Thus, chronic oral treatment with a therapeutically relevant dose of MPH preferentially affected the ventral part of the hippocampus and induced contrasting effects in adolescent and adult rats. The differences in behavior were paralleled by opposite effects on adult neurogenesis and granule cell proliferation.